Bridging the brain and gut: neuroimmune mechanisms of neuroinflammation and therapeutic insights - Müller, Ludmila; Di Benedetto, Svetlana (Frontiers in Cellular Neuroscience, 2025)
The central nervous system (CNS) and the immune system are profoundly interconnected, engaging in a continuous dynamic exchange that regulates homeostasis, immune surveillance, and responses to injury. These interactions occur through diverse mechanisms, ranging from microglial activation and cytokine signaling to peripheral immune cell infiltration. When disrupted, this balance contributes to neurodegenerative processes, affecting cognitive function and neuronal survival. This mini-review examines the cellular and molecular foundations of neuroimmune communication, focusing on how neuroimmune interactions influence the onset and progression of neurodegenerative disorders such as Alzheimer’s disease. Key mechanisms include barrier systems, gut-brain interactions, and circadian rhythm regulation, all playing a crucial role in modulating neuroinflammatory responses. The gut-brain axis plays a pivotal role in modulating CNS function, as alterations in gut microbiota composition can trigger neuroinflammatory pathways, affect systemic immunity, and influence disease susceptibility. Both innate and adaptive immune responses are instrumental in shaping disease trajectory, highlighting the complex interplay between systemic and neural immune components. The blood-brain barrier and glymphatic system modulate immune cell trafficking and waste clearance, influencing CNS pathology. Additionally, circadian rhythm and sleep patterns regulate neuroimmune balance, with disruptions exacerbating inflammation and neurodegeneration. Neuroimmune crosstalk manifests through a spectrum of pathways, each capable of either promoting resilience or accelerating neurodegeneration. By unraveling these connections, we can gain new insights into potential strategies to modulate immune responses and restore homeostasis. This investigation underlines the necessity of integrative approaches that target immune modulation, microbiota regulation, and circadian alignment to mitigate neurodegenerative disease progression and improve therapeutic outcomes.